Novel loop-like aromatic compounds: a further step on the road to nanobelts and nanotubes - Rajuri, Venkataramana; Ajami, Dariush; Schaller, Gaston R.; Näther, Christian; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2010)
The synthesis and crystal structural characterization of new compounds 2–6 were accomplished. As a common synthetic methodology, the Diels–Alder reaction was applied to 9,9′,10,10′-tetradehydrodianthracene (TDDA) (7) to furnish the [12]annulenes 2 and 3 [16]annulene 6 and adduct 5.
Keywords: [n]annulenes; Diels–Alder reaction; nanobelts; tetradehydrodianthracene

(untitled) - Scott, L. T. (Angew. Chem., 2003)
Angew. Chem., Int. Ed.2003, 42,4133–4135. doi:10.1002/anie.200301671

Modern Cyclophane Chemistry - Herges, R. (Fully Conjugated Beltenes (Belt-Like and Tubular Aromatics), 2004)

(untitled) - Kammermeier, S.; Jones, P. G.; Herges, R. (Angew. Chem., 1997)
Angew. Chem., Int. Ed. Engl.1997, 36,1757–1760. doi:10.1002/anie.199717571

(untitled) - Kammermeier, S.; Jones, P. G.; Herges, R. (Angew. Chem., 1996)
Angew. Chem., Int. Ed. Engl.1996, 35,2669–2671. doi:10.1002/anie.199626691

(untitled) - Kawase, T.; Darabi, H. R.; Oda, M. (Angew. Chem., 1996)
Angew. Chem., Int. Ed. Engl.1996, 35,2664–2666. doi:10.1002/anie.199626641

(untitled) - Esser, B.; Rominger, F.; Gleiter, R. (J. Am. Chem. Soc., 2008)

(untitled) - Kohnke, F. H.; Slawin, A. M. Z.; Stoddart, J. F.; Williams, D. J. (Angew. Chem., 1987)
Angew. Chem., Int. Ed. Engl.1987, 26,892–894. doi:10.1002/anie.198708921

(untitled) - Girreser, U.; Giuffrida, D.; Kohnke, F. H.; Mathias, J. P.; Philp, D.; Stoddart, J. F. (Pure Appl. Chem., 1993)

(untitled) - Herges, R. (Nachr. Chem., 2007)

(untitled) - Smalley, R. E.; Li, Y.; Moore, V. C.; Price, B. K.; Colorado, R.; Schmidt, H. K.; Hauge, R. H.; Barron, A. R.; Tour, J. M. (J. Am. Chem. Soc., 2006)

(untitled) - Neudorff, W. D.; Lentz, D.; Anibarro, M.; Schlüter, A. D. (Chem.–Eur. J., 2003)

(untitled) - Schröder, G.; Oth, J. F. M. (Tetrahedron Lett., 1966)

(untitled) - Mehta, G. (J. Chem. Educ., 1982)

(untitled) - Quast, H.; Eckert, P. (Angew. Chem., 1976)
Angew. Chem., Int. Ed. Engl.1976, 15,168–169. doi:10.1002/anie.197601681

(untitled) - Bulusu, B. A. R. C.; Spur, P. R.; Pinkos, R.; Grund, C.; Fessner, W.-D.; Hunkler, D.; Fritz, H.; Roth, W. R.; Prinzbach, H. (Chimia, 1987)

(untitled) - Viavattene, R. L.; Greene, D. F.; Cheung, L. D.; Majeste, R.; Trefonas, L. M. (J. Am. Chem. Soc., 1974)

(untitled) - Deichmann, M.; Näther, C.; Herges, R. (Org. Lett., 2003)

(untitled) - Tahara, K.; Tobe, Y. (Chem. Rev., 2006)

(untitled) - Spitler, E. L.; Johnson, C. A., II; Haley, M. M. (Chem. Rev., 2006)

(untitled) - Kammermeier, S.; Jones, P. G.; Herges, R. (Angew. Chem., 1997)
Angew. Chem., Int. Ed. Engl.1997, 36,2200–2202. doi:10.1002/anie.199722001

(untitled) - Kang, H. C.; Hanson, A. W.; Eaton, B.; Boekelheide, V. (J. Am. Chem. Soc., 1985)

(untitled) - Gross, J.; Harder, G.; Vögtle, F.; Stephan, H.; Gloe, K. (Angew. Chem., 1995)
Angew. Chem., Int. Ed. Engl.1995, 34,481–484. doi:10.1002/anie.199504811

(untitled) - Yoshida, T.; Kuwatani, Y.; Hara, K.; Yoshida, M.; Matsuyama, H.; Iyoda, M.; Nagase, S. (Tetrahedron Lett., 2001)

(untitled) - Raasch, M. S. (J. Org. Chem., 1980)

(untitled) - Lou, J.; Chang, J.; Jorgensen, J.; Lemal, D. M. (J. Am. Chem. Soc., 2002)